HUBUNGAN STATUS GIZI (INDIKATOR IMT) TERHADAP KEJADIAN METABOLIC SYNDROME DI PONDOK PESANTREN AL-HIDAYAH, KABUPATEN NGAWI 2018 - Choirotussanijah Choirotussanijah; Hotimah Hotimah (UNUSA Press, 2019)
Metabolic syndrome is a complex metabolic disorder that is caused by obesity. Body mass index could be simple indicator and very recommended for assessed nutritional state. This study aim to found correlation between nutritional state using BMI to total metabolic syndrome in Pesantren Al Hidayah Kabupaten Ngawi, East Java. Beside, this study is expected could give information for medical officer, especially in Kabupaten Ngawi area as a strategy to prevent metabolic disorder and as new knowledge for peoples in Pesantren Al Hidayah area. Study design using analytic descriptive. Study run in Juni-July 2018 with participants came from population in Pesantren area. We get data about abdomen circumference, body weigh and height, blood pressure, and blood glucose. From 72 participants, 3 participants is suspected suffer from metabolic syndrome, while 61 other was not. The results did not show significancy in statistic. However, the others study showed significant result for correlation nutritional state and body mass index.